Fruit production and biochemical aspects of seeds of Euryale ferox Salisb. under ex-situ conditions (Bangladesh Journal of Botany, 2008)
Ex-situ culture studies of Euryale ferox Salisb. using fresh mature seeds were carried out in an arboretum. Production of fresh fruit has been estimated to be 3.05 t/ha. Biochemical analysis of the seeds revealed 61% carbohydrate, 15.6% protein, 12.1% moisture, 7.6% fibre, 1.8% ash and 1.35% fat. The seeds were found to contain 12 amino acids, which are histidine, leucine, isoleucine, glutamic acid, lysine, tyrosine, valine, aspartic, threonine, alanine, methionine and arginine. Key words: Euryale ferox, Ex-situ culture, Fruit production, Seeds biochemical content doi:10.3329/bjb.v37i2.1727 Bangladesh J. Bot. 37(2): 179-181, 2008 (December)